CD44+ cells determine fenofibrate‐induced microevolution of drug‐resistance in prostate cancer cell populations. (2nd October 2020) - Wróbel, Tomasz; Luty, Marcin; Catapano, Jessica; Karnas, Elżbieta; Szczygieł, Małgorzata; Piwowarczyk, Katarzyna; Ryszawy, Damian; Drabik, Grażyna; Zuba‐Surma, Ewa; Siedlar, Maciej; Madeja, Zbigniew; Elas, Martyna; et al.
Abstract: Combinations of metabolic blockers (including fenofibrate) with chemotherapeutic drugs interfere with the drug‐resistance of prostate cancer cells. However, their effect on cancer stem cells‐dependent microevolution of prostate cancer malignancy remains unaddressed. Here, we hypothesize that the combined docetaxel/fenofibrate treatment prompts the selective expansion of cancer stem cells that affects the microevolution of their progenies. Accordingly, we adapted a combined in vitro/in vivo approach to identify biological and therapeutic consequences of this process. Minute subpopulations of docetaxel‐resistant CD133 high and/or CD44 high cancer stem cell‐like (SCL) cells were found in prostate cancer DU145 and PC3 cell populations. When pretreated with docetaxel, they readily differentiated into docetaxel‐resistant CD44 negative "bulk" cells, thus accounting for the microevolution of drug‐resistant cell lineages. Combined docetaxel/fenofibrate treatment induced the generation of poly(morpho)nuclear giant cells and drug‐resistant CD44 high SCL cells. However, the CD44 negative offspring of docetaxel‐ and docetaxel/fenofibrate‐treated SCLs remained relatively sensitive to the combined treatment, while retaining enhanced resistance to docetaxel. Long‐term propagation of drug‐resistant SCL‐derived lineages in the absence of docetaxel/fenofibrate resulted in their reverse microevolution toward the drug‐sensitivity and invasive phenotype. Consequently, prostate tumors were able to recover from the combined docetaxel/fenofibrate stress after the initial arrest of their expansion in vivo. In conclusion, we have confirmed the potential of fenofibrate for the metronomic treatment of drug‐resistant prostate tumors. However, docetaxel/fenofibrate‐induced selective expansion of hyper‐resistant CD44 high SCL prostate cells and their "bulk" progenies prompts the microevolution of prostate tumor drug‐resistance. This process can limit the implementation of metabolic chemotherapy in prostate cancer treatment. Abstract : CD44 + stem cell‐related microevolution of prostate cancer drug‐resistance under the combined chemotherapeutic/metabolic stress. Combined (DCX)/fenofibrate (FF) treatment induces the formation of polymorphonuclear cells (upper insert) and DCX/FF‐resistant CD44 + /CD133 + SCL cells (lower insert) that give rise to DCX‐ (but not DCX/FF‐) "super‐resistant" cell populations (right).